Feasibility and Efficacy of Craniosacral Therapy on Sleep Quality in Fibromyalgia Syndrome: a Pre-Post Pilot Trial - Ughreja, Reepa Avichal; Venkatesan, Prem; Gopalakrishna, Dharmanand Balebail; Singh, Yogesh Preet (International Journal of Therapeutic Massage & Bodywork, 2023)
Background: Sleep disturbance is one of the key symptoms of fibromyalgia syndrome (FMS), which negatively affects the participants’ quality of life. Craniosacral therapy (CST) is a gentle manual technique found to have significant effects on pain and function in chronic pain participants. However, limited evidence exists on its effectiveness on sleep quality in FMS participants. Purpose: To evaluate the feasibility and effectiveness of CST on sleep quality in FMS participants. Setting: Outpatient physiotherapy department of a hospital in Bangalore. Participants: Participants diagnosed with FMS. Research Design: A pre/post pilot trial. Intervention: Once weekly, 45-minute sessions of CST for 12 weeks. The participants continued the standard medical care prescribed by the physician. Main Outcome Measure: The sleep quality was evaluated using Pittsburgh Sleep Quality Index (PSQI) at baseline and 12 weeks. The data analysis was carried out using paired t test. Results: 9 out of 10 included par-ticipants completed the treatment and were included for analysis. The results of the paired t test showed significant improvement in the global PSQI score (p = .001, mean difference = 5.44±3.28, 95% CI = 2.92-7.97), as well as the 5 components of PSQI (p < .05). Conclusion: CST was feasible to deliver with high retention, acceptability, and minimal adverse events. It significantly improved sleep quality in FMS participants along with standard medical care. However, future studies with larger sample sizes and appropriate control groups are required to confirm the findings.